Preparation method of composite material for synergistically degrading ibuprofen in sewage through ozone photocatalysis
By loading polyo-cyanobenzoic acid benzoic acid, hydroxy-modified graphyne GDY-xOH and CoCu2Se4Sn crystals on the surface of the foam nickel matrix, a composite material is formed. The ozone photocatalytic synergistic degradation technology is used to solve the problem of removing cloth in the existing technology. The problem of profen sewage has achieved efficient photocatalytic oxidation and synergistic ozone oxidation and degradation.
Patent Information
- Application Number
- CN202411844200.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to efficiently remove ibuprofen-containing sewage, and the ozone oxidation and degradation efficiency is low, making it difficult to effectively treat ibuprofen-containing sewage.
Ozone photocatalytic synergistic degradation technology is used to form composite materials by loading polyo-cyanobenzoic acid benzoic acid, hydroxy-modified graphyne GDY-xOH and CoCu2Se4Sn crystals on the surface of the foam nickel matrix to form a composite material, achieving photocatalytic oxidation and synergistic ozone oxidation degradation.
High efficiency and excellent and stable photocatalytic oxidation and synergistic ozone oxidation degradation of ibuprofen-containing wastewater, significantly improving the removal rate of ibuprofen.
Smart Images

Figure CN119430458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ibuprofen-containing sewage treatment, in particular to a method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage. Background Art
[0002] Ibuprofen is a widely used non-steroidal anti-inflammatory, antipyretic, analgesic and anticoagulant drug. Ibuprofen achieves anti-inflammatory effects by inhibiting the activity of cyclooxygenase and hindering the synthesis of inflammatory mediators such as prostaglandins, prostacyclins and leukotrienes, which are metabolites of arachidonic acid; it achieves analgesic effects by inhibiting the release of inflammatory mediators and the activation of neurons; it achieves antipyretic and cooling effects by affecting the hypothalamic temperature regulation center; it achieves anticoagulant effects by inhibiting platelet adhesion and aggregation. The excretion of unmetabolized ibuprofen and metabolized ibuprofen product hydroxyibuprofen in human medical processes, the production of ibuprofen by pharmaceutical companies and the use of ibuprofen in the aquaculture industry are the root causes of a large amount of wastewater containing ibuprofen. Ibuprofen in wastewater is difficult to biodegrade naturally, has carcinogenic and teratogenic toxicity, and poses a great threat to human health and the aquatic environment.
[0003] Ozone has strong oxidizing properties, and its oxidation potential can be 2.07V. It can directly oxidize and degrade phenolic and amine organic matter containing electron-donating groups, and can also directly oxidize and degrade organic pollutants through the ·OH free radicals generated by its own decay process. However, the types of organic matter that ozone can directly oxidize and degrade are limited, the oxidative degradation is not thorough, the degradation rate is low, and the amount of ·OH free radicals generated by its own decay process is insufficient, making it difficult to effectively oxidize and degrade wastewater containing ibuprofen.
[0004] Photocatalytic degradation of wastewater containing organic pollutants refers to the process in which photocatalytic materials absorb light energy under illumination to produce active substances such as OH free radicals with high oxidizing ability, thereby oxidizing and degrading organic pollutants. Using the photocatalytic oxidation of photocatalytic materials in synergistic with the ozone oxidation degradation effect to degrade ibuprofen wastewater is a new technical approach. However, there is currently a lack of highly efficient, excellent and stable treatment materials and related preparation technologies in the field of ibuprofen wastewater treatment. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in wastewater. The composite material prepared by the method has the performance of high efficiency and excellent and stable photocatalytic oxidation synergistic ozone oxidation degradation of ibuprofen-containing wastewater.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0008] Step [1]: loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate;
[0009] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide);
[0010] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystals.
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide were added to ethanol and mixed to form a base liquid; aniline was added to deionized water and mixed to form an additive liquid; the base liquid and the additive liquid were mixed in a certain proportion to form a synthetic liquid; the nickel foam was immersed in the synthetic liquid and reacted at room temperature for 16-20 hours to obtain a nickel foam having a surface loaded with polybenzoic acid benzamide, which was recorded as intermediate A;
[0013] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution; immerse intermediate A in the substitution reaction solution, heat in a water bath to 50-70°C, react for 8-10 hours, and complete the ortho-cyano substitution of polybenzoic acid phenylamide. Air-dry at room temperature for 6 to 8 hours to obtain a nickel foam with poly-o-cyanobenzoic acid phenylamide loaded on the surface, which is recorded as intermediate B.
[0014] Preferably, in step a1, the amount of ethylene dibenzoate added to each liter of the base liquid is 130-170 g, the amount of ethyl benzoate added is 50-90 mL, and the amount of dibenzoyl peroxide added is 20-40 g; the concentration of aniline in the additive liquid is 160-190 mL / L; the volume ratio between the base liquid and the additive liquid in the synthetic liquid is 7-11:4-6; the weight of the nickel foam substrate immersed in each liter of the synthetic liquid is 260-280 g.
[0015] Preferably, in step a2, the amount of trimethylsilyl cyanide added to each liter of the alternative reaction solution is 140-170 mL, and the amount of ethyl benzoate added is 30-40 mL; the weight of the intermediate A immersed in each liter of the alternative reaction solution is 130-190 g.
[0016] Preferably, the step [2] specifically includes the following operations:
[0017] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetylhydrazine to a solvent consisting of dimethyl sulfoxide and methanol, disperse them evenly by ultrasonication to form a hydroxyl-modified solution; heat to 60-80°C in a water bath, react for 12-14 hours, cool to room temperature, filter the solid phase and dry for 8 to 12 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0018] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 20 to 30 minutes to form a loading liquid; immerse the intermediate B in the loading liquid, and use the intermediate B as the cathode and the stainless steel plate as the anode to electrophoretically deposit at a constant voltage of 40 to 70 V at 20 to 40°C for 10 to 20 minutes to load hydroxyl-modified graphyne GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0019] Preferably, in step b1, the amount of graphyne nanopowder added to each liter of the hydroxyl modified solution is 210-240 g, the amount of 3-hydroxydodecanedioic acid added is 30-50 g, and the amount of hydroxyacetylhydrazine added is 70-120 g; the volume ratio between dimethyl sulfoxide and methanol in the solvent is 1:1.
[0020] Preferably, in step b2, the amount of GDY-xOH added to each liter of the loading liquid is 80-120 g, and the amount of ammonium nitrate added is 15-30 g; the weight of the intermediate B immersed in each liter of the loading liquid is 130-190 g.
[0021] Preferably, the step [3] specifically includes the following operations:
[0022] c1. Add cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride to deionized water and mix to form a crystal assembly solution;
[0023] c2. Immerse the intermediate C in the crystal assembly solution, heat to 70-100°C, react for 8-12 hours, and dry in a drying oven at 40-60°C for 3.5 to 5 hours to complete the CoCu 2 Se 4 The assembly of Sn in GDY-xOH finally obtains the composite material.
[0024] Preferably, in step c1, the cobalt nitrate concentration in the crystal assembly solution is 60-80 g / L, the copper sulfate concentration is 120-150 g / L, the selenic acid concentration is 150-170 g / L, the ammonium tellurate concentration is 90-110 g / L, and the tin chloride concentration is 40-90 mL / L.
[0025] Preferably, in step c2, the weight of the intermediate C immersed in each liter of the crystal assembly solution is 240-260 g.
[0026] The positive effect of the present invention is that the composite material prepared by the method of the present invention is synthesized on the surface of nickel foam poly(o-cyanobenzoic acid benzamide) organic matter and loaded with CoCu 2 Se 4 Sn / GDY-xOH(CoCu 2 Se 4 Sn crystals are assembled on the surface of GDY-xOH), wherein: poly(o-cyanobenzoic acid benzamide) is synthesized by replacing the ortho-cyano group of benzoic acid on the basis of synthesizing poly(o-cyanobenzoic acid benzamide) from dibenzoic acid ethylene glycol monomer and aniline monomer; CoCu 2 Se 4 Sn crystal is tetragonal, space group is I-42m (121); GDY-xOH is hydroxyl-modified graphyne, hydroxyl groups form chemical bonds with carbon atoms of acetylene bonds of graphyne to form hydroxyl-modified GDY-xOH (1≤x≤3). Poly(o-cyanobenzoic acid benzamide) organic matter is a polymer connected by amide groups, which loads CoCu 2 Se 4 Sn / GDY-xOH(CoCu 2 Se 4 The structure of Sn crystals assembled on the GDY-xOH surface can fully expose CoCu 2 Se 4 Sn / GDY-xOH active oxidation degradation sites, and can provide a stable adsorption reaction interface for the photocatalytic oxidation and ozone oxidation degradation process of ibuprofen; at the same time, hydroxyl-modified graphyne GDY-xOH can significantly enhance the adsorption of ibuprofen and directly change the graphyne band gap, which can effectively inhibit the CoCu 2 Se 4 Sn photogenerated electrons and holes recombine; in addition, the acetylene bonds of hydroxyl-modified Graphyne can strongly attract CoCu 2 Se 4 Some electrons of the Sn crystal are close to the acetylene bond, thereby promoting the photocatalytic oxidation process of ibuprofen and effectively improving the photocatalytic activity.
[0027] In conclusion, the composite material prepared according to the present invention has the performance of high efficiency and excellent and stable photocatalytic oxidation synergistic with ozone oxidation to degrade ibuprofen-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the preparation process of the composite material of the present invention;
[0029] Figure 2 Schematic diagram of the microstructure of the composite material of the present invention;
[0030] Figure 3It is the TOC removal rate of the simulated ibuprofen-containing wastewater treated by Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0031] Figure 4a , 4b 4 and 4c are relationship diagrams between the number of uses and TOC removal rate when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated ibuprofen-containing wastewater. DETAILED DESCRIPTION
[0032] Reference Figure 1 The present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0033] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0034] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 130-170 g, the amount of ethyl benzoate added is 50-90 mL, and the amount of dibenzoyl peroxide added is 20-40 g); aniline is added to deionized water and mixed to form an aniline concentration of 160-190 mL / L of an additive solution; the base liquid and the additive solution are mixed in a volume ratio of 7-11:4-6 to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 260-280 g), and the reaction is carried out at room temperature for 16-20 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0035] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added per liter of the substitution reaction solution is 140-170 mL, and the amount of ethyl benzoate added is 30-40 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 130-190 g), heat to 50-70 ° C in a water bath, react for 8-10 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 6 to 8 hours to obtain a nickel foam with poly-o-cyanobenzoic acid benzamide loaded on the surface, recorded as intermediate B.
[0036] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0037] b1. Adding graphene nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and uniformly dispersing by ultrasonication to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide to methanol in the solvent is 1:1, and the amount of graphene nanopowder added to each liter of the hydroxyl-modified solution is 210-240 g, the amount of 3-hydroxydodecanedioic acid added is 30-50 g, and the amount of hydroxyacetyl hydrazide added is 70-120 g; heating in a water bath to 60-80° C., reacting for 12-14 hours, cooling to room temperature, filtering the solid phase and drying for 8-12 hours to obtain hydroxyl-modified graphene GDY-xOH (1≤x≤3).
[0038] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 20 to 30 minutes to form a loading liquid, wherein the amount of GDY-xOH added to each liter of the loading liquid is 80 to 120 g and the amount of ammonium nitrate added is 15 to 30 g; immerse the intermediate B in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 130-190 g), and use the intermediate B as the cathode and the stainless steel plate as the anode, and perform electrophoretic deposition at a constant voltage of 40 to 70 V at 20 to 40° C. for 10 to 20 minutes to load hydroxyl-modified graphene GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0039] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystal, specifically including the following operations:
[0040] c1. Add cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride to deionized water to form a crystal assembly solution having a cobalt nitrate concentration of 60 to 80 g / L, a copper sulfate concentration of 120 to 150 g / L, a selenic acid concentration of 150 to 170 g / L, an ammonium tellurate concentration of 90 to 110 g / L, and a tin chloride concentration of 40 to 90 mL / L;
[0041] c2. Immerse the intermediate C in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 240-260g), heat to 70-100°C, react for 8-12 hours, and dry in a drying oven at 40-60°C for 3.5 to 5 hours to complete CoCu 2 Se 4 Sn was assembled on GDY-xOH to finally obtain the composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY-xOH), the microstructure diagram is shown in Figure 2 shown.
[0042] The preferred embodiments of the present invention are described below by way of example.
[0043] Example 1
[0044] Preferred embodiment 1 of the present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0045] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0046] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 150g, the amount of ethyl benzoate added is 80mL, and the amount of dibenzoyl peroxide added is 30g); aniline is added to deionized water and mixed to form an aniline concentration of 190mL / L of an additive solution; the base liquid and the additive solution are mixed in a ratio of 11:6 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 275g), and the reaction is carried out at room temperature for 18 hours to obtain a nickel foam with a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0047] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 150 mL, and the amount of ethyl benzoate added is 35 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 170 g), heat to 60° C. in a water bath, react for 10 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 8 hours to obtain a nickel foam loaded with poly-o-cyanobenzoic acid benzamide on the surface, recorded as intermediate B.
[0048] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0049] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and disperse them evenly by ultrasonic dispersion to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide and methanol in the solvent is 1:1, and the amount of graphyne nanopowder added to each liter of the hydroxyl-modified solution is 230 g, the amount of 3-hydroxydodecanedioic acid added is 40 g, and the amount of hydroxyacetyl hydrazide added is 100 g; heat in a water bath to 70° C., react for 13 hours, cool to room temperature, filter the solid phase and dry for 10 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0050] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 25 minutes to form a loading liquid, wherein the amount of GDY-xOH added to each liter of the loading liquid is 90 g and the amount of ammonium nitrate added is 20 g; immerse the intermediate B in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 150 g), and use the intermediate B as the cathode and the stainless steel plate as the anode to electrophoretically deposit at a constant voltage of 60 V at 30° C. for 15 minutes to load hydroxyl-modified graphene GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0051] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystal, specifically including the following operations:
[0052] c1. Cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride were added to deionized water to form a crystal assembly solution having a cobalt nitrate concentration of 70 g / L, a copper sulfate concentration of 140 g / L, a selenic acid concentration of 160 g / L, an ammonium tellurate concentration of 100 g / L, and a tin chloride concentration of 80 mL / L;
[0053] c2. The intermediate C is immersed in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 252g), heated to 90°C, reacted for 10 hours, and dried in a drying oven at 50°C for 4 hours to complete the CoCu 2 Se 4 Sn was assembled on GDY-xOH to finally obtain the composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY-xOH), recorded as Example 1.
[0054] Comparative Example 1
[0055] This comparative example 1 provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0056] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0057] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 140g, the amount of ethyl benzoate added is 60mL, and the amount of dibenzoyl peroxide added is 30g); aniline is added to deionized water and mixed to form an additive solution having an aniline concentration of 170mL / L; the base liquid and the additive solution are mixed in a ratio of 7:4 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 270g), and the reaction is carried out at room temperature for 18 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0058] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 160 mL, and the amount of ethyl benzoate added is 34 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 170 g), heat to 55° C. in a water bath, react for 9 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 6 hours to obtain a nickel foam with poly-o-cyanobenzoic acid benzamide loaded on the surface, recorded as intermediate B.
[0059] Step [2] loading graphene GDY on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0060] Graphene oxide GDY and ammonium nitrate are added to ethanol and ultrasonically dispersed for 22 minutes at room temperature to form a loading liquid, wherein the amount of GDY added to each liter of the loading liquid is 90 g and the amount of ammonium nitrate added is 20 g; the intermediate B is immersed in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 140 g), and the intermediate B is used as the cathode and the stainless steel plate is used as the anode, and electrophoretic deposition is performed at a constant voltage of 50 V at 30°C for 14 minutes to load graphene oxide GDY on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained foamed nickel-based product is recorded as intermediate C.
[0061] Step [3] Assemble CoCu on the GDY surface 2 Se 4 Sn crystal, specifically including the following operations:
[0062] c1. Cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride were added to deionized water to form a cobalt nitrate concentration of 70 g / L, copper sulfate concentration of 130 g / L, selenic acid concentration of 160 g / L, ammonium tellurate concentration of 100 g / L, tin chloride concentration of 50 mL / L of crystal assembly solution;
[0063] c2. The intermediate C is immersed in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 245g), heated to 80°C, reacted for 10 hours, and dried in a drying oven at 50°C for 4 hours to complete the CoCu 2 Se 4 The composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY), recorded as Comparative Example 1.
[0064] Comparative Example 2
[0065] This comparative example 2 provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0066] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0067] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 160g, the amount of ethyl benzoate added is 80mL, and the amount of dibenzoyl peroxide added is 40g); aniline is added to deionized water and mixed to form an additive solution having an aniline concentration of 170mL / L; the base liquid and the additive solution are mixed in a ratio of 8:5 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 270g), and the reaction is carried out at room temperature for 18 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0068] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 150 mL, and the amount of ethyl benzoate added is 35 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 170 g), heat to 60° C. in a water bath, react for 9 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 7 hours to obtain a nickel foam with poly-o-cyanobenzoic acid benzamide loaded on the surface, recorded as intermediate B.
[0069] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0070] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and disperse them evenly by ultrasonic dispersion to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide and methanol in the solvent is 1:1, and the amount of graphyne nanopowder added to each liter of the hydroxyl-modified solution is 230 g, the amount of 3-hydroxydodecanedioic acid added is 40 g, and the amount of hydroxyacetyl hydrazide added is 110 g; heat in a water bath to 70° C., react for 14 hours, cool to room temperature, filter the solid phase and dry for 10 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0071] b2. GDY-xOH and ammonium nitrate are added to ethanol and ultrasonically dispersed for 25 minutes at room temperature to form a load liquid, wherein the amount of GDY-xOH added per liter of the load liquid is 90 g and the amount of ammonium nitrate added is 20 g; the intermediate B is immersed in the load liquid (the weight of the intermediate B immersed in the load liquid per liter is 160 g), and the intermediate B is used as the cathode and the stainless steel plate is used as the anode, and electrophoretic deposition is performed at a constant voltage of 60V at 35°C for 15 minutes to load hydroxyl-modified graphene GDY-xOH on the surface of poly-o-cyanobenzoic acid benzamide, and the obtained foamed nickel-based product is the composite material (foamed nickel-based poly-o-cyanobenzoic acid benzamide loaded with GDY-xOH), which is recorded as Comparative Example 2.
[0072] In order to analyze the performance of ozone / photocatalytic synergistic oxidation degradation of ibuprofen-containing sewage in Example 1, Comparative Example 1 and Comparative Example 2, ibuprofen was added to deionized water to form a simulated ibuprofen-containing sewage with an ibuprofen addition of 5 mg / L. 100 ml of simulated ibuprofen-containing sewage was poured into a beaker, 5 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed in a beaker, and the ozone generator was produced. The concentration of 10 mg / L ozone was input into each simulated ibuprofen-containing sewage at a flow rate of 60 ml / min. At the same time, a xenon light source was used under the conditions of a working current of 20 A and a working voltage of 20 V. Ultraviolet light (λ = 350 nm) and visible light (λ = 530 nm) were irradiated to Comparative Example 1, Comparative Example 2 and Example 1 for ten minutes, and a dark and lightless experiment was set at the same time. The total organic carbon TOC of the simulated ibuprofen-containing sewage was tested by a total organic carbon (TOC) analyzer. The results are as follows Figure 3 As shown in the figure, it can be seen that the total organic carbon removal rate of Example 1 in the degradation of ibuprofen by ultraviolet light and visible light synergistic ozone oxidation is more than 90%, which is significantly higher than the total organic carbon removal rates of Comparative Examples 1 and 2 under the same conditions (75% and 64%, 35% and 33%), and also significantly higher than the total organic carbon removal rate of ibuprofen by ozone oxidation alone (less than 42%). Under the aforementioned treatment conditions and treatment time, Example 1, Comparative Example 1 and Comparative Example 2 were repeatedly used, and the relationship between the number of uses and the TOC removal rate was as follows: Figure 4a-c, it can be seen from the figure that the total organic carbon removal rate of the simulated ibuprofen-containing wastewater in the fifth treatment under ultraviolet and visible light conditions in Example 1 can also reach more than 86%, while the TOC removal rate of the simulated ibuprofen-containing wastewater in the fifth treatment of Comparative Example 1 and Comparative Example 2 is significantly reduced.
[0073] In summary, the composite material prepared according to the present invention has the performance of high efficiency and excellent and stable photocatalytic oxidation synergistic with ozone oxidation to degrade ibuprofen-containing wastewater.
[0074] To illustrate in further detail, three additional examples are provided below.
[0075] Example 2
[0076] Preferred embodiment 2 of the present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0077] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0078] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 130g, the amount of ethyl benzoate added is 50mL, and the amount of dibenzoyl peroxide added is 40g); aniline is added to deionized water and mixed to form an additive solution having an aniline concentration of 160mL / L; the base liquid and the additive solution are mixed in a ratio of 7:4 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 260g), and the reaction is carried out at room temperature for 20 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0079] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 140 mL, and the amount of ethyl benzoate added is 40 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 130 g), heat to 70° C. in a water bath, react for 8 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 8 hours to obtain a nickel foam loaded with poly-o-cyanobenzoic acid benzamide on the surface, recorded as intermediate B.
[0080] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0081] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and disperse them evenly by ultrasonic dispersion to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide and methanol in the solvent is 1:1, and the amount of graphyne nanopowder added to each liter of the hydroxyl-modified solution is 240 g, the amount of 3-hydroxydodecanedioic acid added is 30 g, and the amount of hydroxyacetyl hydrazide added is 70 g; heat in a water bath to 80° C., react for 12 hours, cool to room temperature, filter the solid phase and dry for 8 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0082] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 20 minutes to form a loading liquid, wherein the amount of GDY-xOH added to each liter of the loading liquid is 120 g and the amount of ammonium nitrate added is 15 g; immerse the intermediate B in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 130 g), and use the intermediate B as the cathode and the stainless steel plate as the anode to perform electrophoretic deposition at a constant voltage of 70 V at 40° C. for 10 minutes to load hydroxyl-modified graphyne GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0083] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystal, specifically including the following operations:
[0084] c1. Cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride were added to deionized water to form a crystal assembly solution having a cobalt nitrate concentration of 60 g / L, a copper sulfate concentration of 150 g / L, a selenic acid concentration of 170 g / L, an ammonium tellurate concentration of 90 g / L, and a tin chloride concentration of 40 mL / L;
[0085] c2. The intermediate C is immersed in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 240g), heated to 70°C, reacted for 12 hours, and dried in a drying oven at 60°C for 3.5 hours to complete the CoCu 2 Se 4 Sn was assembled on GDY-xOH to finally obtain the composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY-xOH).
[0086] Example 3
[0087] Preferred embodiment 3 of the present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0088] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0089] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 170g, the amount of ethyl benzoate added is 90mL, and the amount of dibenzoyl peroxide added is 20g); aniline is added to deionized water and mixed to form an additive solution having an aniline concentration of 190mL / L; the base liquid and the additive solution are mixed in a ratio of 11:4 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 280g), and the reaction is carried out at room temperature for 16 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0090] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 170 mL, and the amount of ethyl benzoate added is 30 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 190 g), heat to 50° C. in a water bath, react for 10 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 6 hours to obtain a nickel foam loaded with poly-o-cyanobenzoic acid benzamide on the surface, recorded as intermediate B.
[0091] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0092] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and disperse them evenly by ultrasonic dispersion to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide and methanol in the solvent is 1:1, and the amount of graphyne nanopowder added to each liter of the hydroxyl-modified solution is 210 g, the amount of 3-hydroxydodecanedioic acid added is 50 g, and the amount of hydroxyacetyl hydrazide added is 120 g; heat in a water bath to 60° C., react for 14 hours, cool to room temperature, filter the solid phase and dry for 12 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0093] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 30 minutes to form a loading liquid, wherein the amount of GDY-xOH added to each liter of the loading liquid is 80 g and the amount of ammonium nitrate added is 30 g; immerse the intermediate B in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 190 g), and use the intermediate B as the cathode and the stainless steel plate as the anode to perform electrophoretic deposition at a constant voltage of 40V at 20°C for 20 minutes to load hydroxyl-modified graphyne GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0094] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystal, specifically including the following operations:
[0095] c1. Cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride were added to deionized water to form a crystal assembly solution having a cobalt nitrate concentration of 80 g / L, a copper sulfate concentration of 120 g / L, a selenic acid concentration of 150 g / L, an ammonium tellurate concentration of 110 g / L, and a tin chloride concentration of 90 mL / L;
[0096] c2. The intermediate C is immersed in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 260g), heated to 100°C, reacted for 8 hours, and dried in a drying oven at 40°C for 5 hours to complete the CoCu 2 Se 4 Sn was assembled on GDY-xOH to finally obtain the composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY-xOH).
[0097] Example 4
[0098] Preferred embodiment 4 of the present invention provides a method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, comprising the following steps:
[0099] Step [1] loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate specifically comprises the following operations:
[0100] a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide are added to ethanol and mixed to form a base liquid (the amount of ethylene dibenzoate added per liter of the base liquid is 150g, the amount of ethyl benzoate added is 70mL, and the amount of dibenzoyl peroxide added is 30g); aniline is added to deionized water and mixed to form an additive solution having an aniline concentration of 175mL / L; the base liquid and the additive solution are mixed in a ratio of 9:5 by volume to form a synthetic solution; the nickel foam is immersed in the synthetic solution (the weight of the nickel foam substrate immersed in the synthetic solution per liter is 270g), and the reaction is carried out at room temperature for 18 hours to obtain a nickel foam having a surface load of polybenzoic acid phenylamide, which is recorded as intermediate A;
[0101] a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution (the amount of trimethylsilyl cyanide added to each liter of the substitution reaction solution is 155 mL, and the amount of ethyl benzoate added is 35 mL); immerse the intermediate A in the substitution reaction solution (the weight of the intermediate A immersed in each liter of the substitution reaction solution is 160 g), heat to 60° C. in a water bath, react for 9 hours, and complete the ortho-cyano substitution of polybenzoic acid benzamide. Air-dry at room temperature for 7 hours to obtain a nickel foam with poly-o-cyanobenzoic acid benzamide loaded on the surface, recorded as intermediate B.
[0102] Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide) specifically comprises the following operations:
[0103] b1. Add graphyne nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetyl hydrazide to a solvent consisting of dimethyl sulfoxide and methanol, and disperse them evenly by ultrasonic dispersion to form a hydroxyl-modified solution, wherein the volume ratio of dimethyl sulfoxide and methanol in the solvent is 1:1, and the amount of graphyne nanopowder added to each liter of the hydroxyl-modified solution is 225 g, the amount of 3-hydroxydodecanedioic acid added is 40 g, and the amount of hydroxyacetyl hydrazide added is 95 g; heat in a water bath to 70° C., react for 13 hours, cool to room temperature, filter the solid phase and dry for 10 hours to obtain hydroxyl-modified graphyne GDY-xOH (1≤x≤3).
[0104] b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 25 minutes to form a loading liquid, wherein the amount of GDY-xOH added to each liter of the loading liquid is 100 g and the amount of ammonium nitrate added is 22 g; immerse the intermediate B in the loading liquid (the weight of the intermediate B immersed in each liter of the loading liquid is 160 g), and use the intermediate B as the cathode and the stainless steel plate as the anode to perform electrophoretic deposition at a constant voltage of 55 V at 30° C. for 15 minutes to load hydroxyl-modified graphene GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
[0105] Step [3] Assembling CoCu on the surface of GDY-xOH 2 Se 4 Sn crystal, specifically including the following operations:
[0106] c1. Cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride were added to deionized water to form a crystal assembly solution having a cobalt nitrate concentration of 70 g / L, a copper sulfate concentration of 135 g / L, a selenic acid concentration of 160 g / L, an ammonium tellurate concentration of 100 g / L, and a tin chloride concentration of 65 mL / L;
[0107] c2. The intermediate C is immersed in the crystal assembly solution (the weight of the intermediate C immersed in each liter of the crystal assembly solution is 252g), heated to 85°C, reacted for 10 hours, and dried in a drying oven at 50°C for 4 hours to complete the CoCu 2 Se 4 Sn was assembled on GDY-xOH to finally obtain the composite material (foamed nickel-based poly(o-cyanobenzoic acid benzamide) loaded with CoCu 2 Se 4 Sn / GDY-xOH).
[0108] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage, characterized in that: The following steps are included: Step [1]: loading poly(o-cyanobenzoic acid benzamide) on the surface of the nickel foam substrate; Step [2] loading hydroxyl-modified graphene GDY-xOH on the surface of the poly(o-cyanobenzoic acid benzamide); Step [3] Assemble CoCu2Se4Sn crystals on the GDY-xOH surface.
2. The method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Ethylene dibenzoate, ethyl benzoate and dibenzoyl peroxide were added to ethanol and mixed to form a base liquid; aniline was added to deionized water and mixed to form an additive liquid; the base liquid and the additive liquid were mixed in a certain proportion to form a synthetic liquid; the nickel foam was immersed in the synthetic liquid and reacted at room temperature for 16-20 hours to obtain a nickel foam having a surface loaded with polybenzoic acid benzamide, which was recorded as intermediate A; a2. Add trimethylsilyl cyanide and ethyl benzoate to chloroform and mix to form a substitution reaction solution; immerse intermediate A in the substitution reaction solution, heat in a water bath to 50-70°C, react for 8-10 hours, and complete the ortho-cyano substitution of polybenzoic acid phenylamide. Air-dry at room temperature for 6 to 8 hours to obtain a nickel foam with poly-o-cyanobenzoic acid phenylamide loaded on the surface, which is recorded as intermediate B.
3. The method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage according to claim 2, characterized in that: In step a1, the amount of ethylene dibenzoate added per liter of the base liquid is 130-170 g, the amount of ethyl benzoate added is 50-90 mL, and the amount of dibenzoyl peroxide added is 20-40 g; the concentration of aniline in the additive liquid is 160-190 mL / L; the volume ratio between the base liquid and the additive liquid in the synthetic liquid is 7-11:4-6; the weight of the nickel foam substrate immersed in each liter of the synthetic liquid is 260-280 g.
4. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 2, characterized in that: In step a2, the amount of trimethylsilyl cyanide added to each liter of the alternative reaction solution is 140-170 mL, and the amount of ethyl benzoate added is 30-40 mL; the weight of the intermediate A immersed in each liter of the alternative reaction solution is 130-190 g.
5. The method for preparing a composite material for ozone photocatalytic synergistic degradation of ibuprofen in sewage according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add Graphene nanopowder, 3-hydroxydodecanedioic acid and hydroxyacetylhydrazine to a solvent consisting of dimethyl sulfoxide and methanol, disperse uniformly by ultrasonication to form a hydroxyl-modified solution; heat in a water bath to 60-80°C, react for 12-14 hours, cool to room temperature, filter the solid phase and dry for 8 to 12 hours to obtain hydroxyl-modified Graphene GDY-xOH (1≤x≤3); b2. Add GDY-xOH and ammonium nitrate to ethanol and disperse them by ultrasonic at room temperature for 20 to 30 minutes to form a loading liquid; immerse the intermediate B in the loading liquid, and use the intermediate B as the cathode and the stainless steel plate as the anode to electrophoretically deposit at a constant voltage of 40 to 70 V at 20 to 40°C for 10 to 20 minutes to load hydroxyl-modified graphyne GDY-xOH on the surface of poly(o-cyanobenzoic acid benzamide), and the obtained nickel-based foam product is recorded as intermediate C.
6. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 5, characterized in that: In step b1, the amount of graphyne nanopowder added to each liter of the hydroxyl modified solution is 210-240 g, the amount of 3-hydroxydodecanedioic acid added is 30-50 g, and the amount of hydroxyacetylhydrazine added is 70-120 g; the volume ratio between dimethyl sulfoxide and methanol in the solvent is 1:
1.
7. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 5, characterized in that: In step b2, the amount of GDY-xOH added to each liter of the loading liquid is 80-120 g, and the amount of ammonium nitrate added is 15-30 g; the weight of the intermediate B immersed in each liter of the loading liquid is 130-190 g.
8. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add cobalt nitrate, copper sulfate, selenic acid, ammonium tellurate and tin chloride to deionized water and mix to form a crystal assembly solution; c2. Immerse the intermediate C in the crystal assembly solution, heat to 70-100°C, react for 8-12 hours, and dry in a drying oven at 40-60°C for 3.5 to 5 hours to complete the assembly of CoCu2Se4Sn in GDY-xOH, and finally obtain the composite material.
9. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 8, characterized in that: In step c1, the cobalt nitrate concentration in the crystal assembly solution is 60-80 g / L, the copper sulfate concentration is 120-150 g / L, the selenic acid concentration is 150-170 g / L, the ammonium tellurate concentration is 90-110 g / L, and the tin chloride concentration is 40-90 mL / L.
10. The method for preparing a composite material for ozone-photocatalytic synergistic degradation of ibuprofen in sewage according to claim 8, characterized in that: In step c2, the weight of the intermediate C immersed in each liter of the crystal assembly solution is 240-260 g.
Citation Information
Patent Citations
Preparation method of graphdiyne-loaded monatomic catalyst
CN111490258A
Catalyst as well as preparation method and application thereof
CN117418269A
Preparation method of catalyst for treating waste water containing polychlorinated biphenyl through cooperation of magnetic field and Fenton
CN118904399A
Method for preparing graphene-modified polymethyl methacrylate composite material having ultra-high conductivity
WO2017186127A1